Elastic deformation plays a non-negligible role in Greenland’s outlet glacier flow - Christmann, Julia; Helm, Veit; Khan, Shfaqat Abbas; Kleiner, Thomas; Müller, Ralf; Morlighem, Mathieu; Neckel, Niklas; Rückamp, Martin; Steinhage, Daniel; Zeising, Ole; Humbert, Angelika; Institute of Applied Mechanics, University of Kaiserslautern, Kaiserslautern, Germany; et al. (Communications Earth & Environment, 2021)
Future projections of global mean sea level change are uncertain, partly because of our limited understanding of the dynamics of Greenland’s outlet glaciers. Here we study Nioghalvfjerdsbræ, an outlet glacier of the Northeast Greenland Ice Stream that holds 1.1 m sea-level equivalent of ice. We use GPS observations and numerical modelling to investigate the role of tides as well as the elastic contribution to glacier flow. We find that ocean tides alter the basal lubrication of the glacier up to 10 km inland of the grounding line, and that their influence is best described by a viscoelastic rather than a viscous model. Further inland, sliding is the dominant mechanism of fast glacier motion, and the ice flow induces persistent elastic strain. We conclude that elastic deformation plays a role in glacier flow, particularly in areas of steep topographic changes and fast ice velocities. Ice flow dynamics in Greenland’s outlet glaciers are influenced by elastic deformation, both in the area of tidal influence up to 14 km inland from the grounding line and further upstream, suggest analyses of GPS observations and numerical simulations. Bundesministerium für Bildung und Forschung (Federal Ministry of Education and Research) https://doi.org/10.13039/501100002347 European Union’s Horizon 2020 Research and Innovation Programme https://doi.org/10.1594/PANGAEA.928940 https://nsidc.org/data/IDBMG4 https://gitlab.awi.de/jchristm/viscoelastic-79ng-greenland https://doi.org/10.5281/zenodo.5507115 https://doi.org/10.5281/zenodo.5506953